Synthesis and size control of monodispersed BaTiO3–PVP nanoparticles*. Issue 4 (1st December 2016) - Li, Jinhui; Inukai, Koji; Takahashi, Yosuke; Shin, Woosuck
Abstract: Monodispersed, spherical nanoparticles of the BaTiO3 –polyvinylpyrrolidone (BT–PVP) composite were synthesized through the surface modification of the oxide BT by the polymer PVP, using TiCl4, BaCl2, PVP, and KOH (as the mineralizer) in an aqueous solution. To reduce the size of the particles and ensure that they were monodispersed, the concentrations of the Ba and Ti sources were increased and the reaction parameters such as reaction temperature, reaction time, and KOH concentration were optimized. As a result, monodispersed BT–PVP particles with an average diameter of 114 nm (coefficient of variation, CV = 20.0%) were obtained from a Ba-rich solution ([Ti]/[Ba] = 0.2 M:0.3 M; [KOH] = 1.4 M), and their dynamic light scattering in an aqueous suspension demonstrated that the average diameter was 162 nm (CV = 26.6%). A higher KOH concentration resulted in smaller particles, but the excess KOH promoted particle aggregation and PVP gelation. The mechanism of dispersion and aggregation of BT–PVP will be discussed in detail.